KONTROVERSI SISTEM PEMILIHAN PRESIDEN SECARA LANGSUNG DAN TIDAK LANGSUNG DITINJAU DARI SILA KE EMPAT PANCASILA - Saleh, Asri Muhammad; Shaleh, Ali Ismali; Adyatma, Ilham (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
Democracy is a spirit that reflects that the people hold the highest authority in a country. Indonesia has implemented two Presidential Election systems, namely indirectly and directly (after the Reformation period). However, the phenomenon that is happening right now, the direct election of the President and Vice-President has turned out to be polemic because many parties consider it to conflict with the fourth precepts of the Pancasila. The fourth precepts value of Pancasila is interpreted as an implementation of the Presidential Election system which must be represented through the MPR institution. Related to the problem above the problem to be answered is the controversy over the presidential election system directly and indirectly in terms of the four precepts of the Pancasila. The problem was answered using the method normative legal research and analyzed qualitatively by describing, then comparing data with statutory provisions and the opinions of constitutional law experts. In this study, it was concluded that there was no contradiction between the Pancasila and the 1945 Constitution in the implementation of the Presidential election system implemented in Indonesia, both the direct and indirect presidential election system. Every democratic process based on the principle of people's sovereignty is carried out through consensus and agreement through a constitutional system based on Pancasila values. This happened in the direct Presidential election system which is the desire of the people conveyed to their representatives in the DPR.